lncRNA PRR34-AS1 promotes HCC development via modulating Wnt/β-catenin pathway by absorbing miR-296-5p and upregulating E2F2 and SOX12 - Qin, Minzhen (Mol Ther Nucleic Acids, 2021)
Hepatocellular carcinoma (HCC) belongs to the most frequent cancer with a high death rate worldwide. Thousands of long non-coding RNAs (lncRNAs) have been confirmed to influence the development of human cancers, including HCC. Nevertheless, the biological role of PRR34 antisense RNA 1 (PRR34-AS1) in HCC remains obscure. Here, we observed via quantitative real-time reverse transcriptase polymerase chain reaction (quantitative real-time RT-PCR) that PRR34-AS1 was highly expressed in HCC cells. Functional assays revealed that PRR34-AS1 promoted HCC cell proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) process in vitro and facilitated tumor growth in vivo. In addition, western blot analysis and TOP Flash/FOP Flash reporter assays verified that PRR34-AS1 stimulated Wnt/β-catenin pathway in HCC cells. Furthermore, RNA immunoprecipitation (RIP), RNA pull-down, and luciferase reporter assays uncovered that PRR34-AS1 sequestered microRNA-296-5p (miR-296-5p) to positively modulate E2F transcription factor 2 (E2F2) and SRY-box transcription factor 12 (SOX12) in HCC cells. Importantly, chromatin immunoprecipitation (ChIP) and luciferase reporter assays uncovered that E2F2 transcriptionally activated PRR34-AS1 in turn. Further, rescue experiments reflected that PRR34-AS1 affected HCC progression through targeting miR-296-5p/E2F2/SOX12/Wnt/β-catenin axis. Our findings found that PRR34-AS1 elicited oncogenic functions in HCC, which indicated that PRR34-AS1 might be a novel therapeutic target for HCC.